Pengaruh Hidro-oseanografi pada Penempatan Terumbu Buatan di Kawasan Pantai Indonesia - Rachman, Taufiqur; Suleman, Siti Arifaini; Nur, Fitrahwati (Departemen Teknik Kelautan Universitas Hasanuddin, 2024)
The existence of artificial reefs in coastal areas is used to repair damaged habitats by simulating the ecological role of natural coral reefs. The selection of placement locations under the sea is done so that artificial reefs can function properly. The purpose of this study was to determine the influence of hydro-oceanographic characteristics on the placement of artificial reefs that have been carried out in several coastal areas in Indonesia. This research is expected to provide an overview of the effectiveness of artificial reef placement towards efforts to repair damage to the coastal ecosystem. Artificial reef data was obtained in coastal waters located in Java and Sulawesi Island. Review of the application of artificial reefs includes placement location, hydro-oceanographic data, and evaluation of the existing condition of artificial reefs after the sinking period. The review of the relationship between the initial data and the existing condition of artificial reefs after the sinking period at the placement site against the hydro-oceanographic characteristics of the respective coastal water location. The success of artificial reef placement as a coastal ecosystem restoration effort is strongly influenced by bathymetry contours, wave height, current speed, and sedimentation.